2014
DOI: 10.1136/archdischild-2014-307384.543
|View full text |Cite
|
Sign up to set email alerts
|

PS-244a Is Vitamin D Deficiency A Risk Factor For Urinary Tract Infection In Children?

Abstract: After 48 h of treatment a significant decline in bicarbonate levels (from 35,3 ± 4,7 to 31,1 ± 3,9 mmol/L, p < 0,001), pH (from 7,45 ± 0,05 to 7,41 ± 0,06, p < 0,001), and PCO2 (from 52.9 ± 10 to 51,2 ± 10 mmHg, p = 0,002) were found, whereas anion GAP increased (from 6,8 ± 9,8 to 8,7 ± 3,8, p = 0,001). Mechanical ventilation was in use in 102 patients, (31,6% were extubated during acetazolamide treatment).Average Acetazolamide dose was 8,46 mg/Kg/day. None of the patients suffered from serious side-effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, in the same study a prevalence of infection was reported higher in girls than boys, which is a known risk factor, and agrees with our observations as more than half of our patients (59%) were female too. This is in accordance with some studies that found significantly lower 25 (OH)D levels in children with UTI compared to controls and supports that VitD deficiency is a risk factor for UTI and especially in girls (12,(197)(198)(199).…”
Section: Utisupporting
confidence: 92%
“…However, in the same study a prevalence of infection was reported higher in girls than boys, which is a known risk factor, and agrees with our observations as more than half of our patients (59%) were female too. This is in accordance with some studies that found significantly lower 25 (OH)D levels in children with UTI compared to controls and supports that VitD deficiency is a risk factor for UTI and especially in girls (12,(197)(198)(199).…”
Section: Utisupporting
confidence: 92%
“…Four of the six included studies showed that serum levels of vitamin D were significantly lower in children with urinary tract infection than that in controls ( 14 16 , 18 ). One study by Noorbakhsh et al ( 17 ) showed no significant differences between the patient and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Although we did not examine the association between age and sex with plasma levels of vitamin D and the risk of UTI in this study, most studies suggest that plasma vitamin D levels vary with age and sex and it could be one of the limitations of this study. Shalaby et al (15), Tekin et al (14), and Georgieva et al (16) showed that serum 25(OH)D3 levels in girls were significantly lower than boys. This difference in this period of life can be due to malnutrition, inadequate exposure to sunlight and the presence of differencein sex chromosomes (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations